1999
DOI: 10.1046/j.1432-1327.1999.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of human chondromodulin‐I, a cartilage‐derived growth modulating factor, and its expression in Chinese hamster ovary cells

Abstract: Bovine chondromodulin‐I (ChM‐I) purified from fetal cartilage stimulated the matrix synthesis of chondrocytes, and inhibited the growth of vascular endothelial cells in vitro. The human counterpart of this bovine growth regulating factor has not been identified. We report here the cloning of human ChM‐I precursor cDNA and its functional expression in Chinese hamster ovary (CHO) cells. We first identified a genomic DNA fragment which encoded the N‐terminus of the ChM‐I precursor, and then isolated human ChM‐I c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 33 publications
6
74
0
Order By: Relevance
“…Type II collagen deposition in matrix-producing carcinoma was limited to lacunar formation regions. Although ChM-I is also a cartilage-specific noncollagenous matrix molecule, 7,8 this molecule was weakly and focally deposited in the matrix of matrix-producing carcinoma. Such findings suggested that the matrix of matrix-producing carcinoma of the breast was similar to that of normal cartilage, but had not matured to that of the hypertrophic zone of growth plate cartilages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type II collagen deposition in matrix-producing carcinoma was limited to lacunar formation regions. Although ChM-I is also a cartilage-specific noncollagenous matrix molecule, 7,8 this molecule was weakly and focally deposited in the matrix of matrix-producing carcinoma. Such findings suggested that the matrix of matrix-producing carcinoma of the breast was similar to that of normal cartilage, but had not matured to that of the hypertrophic zone of growth plate cartilages.…”
Section: Discussionmentioning
confidence: 99%
“…3 This macromolecule deposits in the hypertrophic zones of growth plate cartilage, 4 although it was reported to deposit in the salivary pleomorphic adenoma, which frequently showed mesenchyme-like elements, including myxoid and chondroid tissues. 5,6 Type II collagen, which is a cartilage-specific major collagen, and chondromodulin-I (ChM-I), which is cartilage-specific noncollagenous matrix protein, 4,7,8 are deposited in the normal cartilaginous matrix. These molecules can be useful markers of cartilaginous differentiation.…”
mentioning
confidence: 99%
“…1A, Table 1). CHM1 is a known regulator of cartilage and bone growth and is normally expressed in proliferating and prehypertrophic chondrocytes of the growth plate (21). In bone explants, its overex- pression promotes cartilage deposition but inhibits bone deposition, whereas studies of CHM1 mutant mice show that its deficiency results in increased bone deposition (33,34).…”
Section: Expression Profiles Of Men 2 Tumorsmentioning
confidence: 99%
“…We isolated and purified the factor that promoted this growth inhibition, and subsequent amino acid sequencing identified it as chondromodulin-I (ChM-I) (Hiraki et al, 1991). Transfection of ChM-I precursor cDNAs into either COS7 cells or CHO cells resulted in secretion of mature ChM-I (120 amino acids) as a 25 kDa glycoprotein following processing at the furin cleavage site of the type II membrane ChM-1 precursor protein (Azizan et al, 2001;Hiraki et al, 1997;Hiraki et al, 1999). In situ hybridization and immunohistochemistry indicated that ChM-I is specifically localized in the avascular zone of cartilage during endochondral bone formation Shukunami et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…All eight cysteine residues in the mature ChM-I protein are present in this domain and form four intramolecular disulfide bonds (Hiraki et al, 1991;Neame et al, 1990). These bonds are critical for the bioactivity of ChM-I, which is abrogated by their reduction Hiraki et al, 1999).…”
Section: Introductionmentioning
confidence: 99%